Class II malocclusion occlusal severity description - Guilherme Janson; Renata Sathler; Thais Maria Freire Fernandes; Marcelo Zanda; Arnaldo Pinzan (University of São Paulo, 2010)
OBJECTIVES: It is well known that the efficacy and the efficiency of a Class II malocclusion treatment are aspects closely related to the severity of the dental anteroposterior discrepancy. Even though, sample selection based on cephalometric variables without considering the severity of the occlusal anteroposterior discrepancy is still common in current papers. In some of them, when occlusal parameters are chosen, the severity is often neglected. The purpose of this study is to verify the importance given to the classification of Class II malocclusion, based on the criteria used for sample selection in a great number of papers published in the orthodontic journal with the highest impact factor. MATERIAL AND METHODS: A search was performed in PubMed database for full-text research papers referencing Class II malocclusion in the history of the American Journal of Orthodontics and Dentofacial Orthopedics (AJO-DO). RESULTS: A total of 359 papers were retrieved, among which only 72 (20.06%) papers described the occlusal severity of the Class II malocclusion sample. In the other 287 (79.94%) papers that did not specify the anteroposterior discrepancy severity, description was considered to be crucial in 159 (55.40%) of them. CONCLUSIONS: Omission in describing the occlusal severity demands a cautious interpretation of 44.29% of the papers retrieved in this study.